Strategi Peningkatan Volume Penjualan UMKM Keripik Pisang Definas di Era Pandemi Covid-19 - Rahma Ulfa Maghfiroh (Al-Muraqabah: Journal of Management and Sharia Business, 2022)
The MSMEs of definas banana chips have to be able to survive and compete during the COVID-19 pandemic. This study aims to identify the implementation of the 4P marketing mix in an effort to increase sales volume of Definas banana chips during the covid-19 pandemic, as well as analyze effective and efficient marketing strategies to be able to compete with competitors. The method uses descriptive qualitative through observation, document study, and in-depth interviews with business actors and several consumers of Definas banana chips. The results showed that the marketing strategy in the form of a marketing mix consisting of product, price, place and promotion carried out by Definas banana chips was able to survive the covid-19 pandemic. There are still several strategies that must be improved related to products and promotions in order to increase the competitiveness of Definas banana chips products.